Laba Perusahaan dan Analisis Faktor-Faktor yang Memengaruhinya - Djamali, Hisnol; Alhamidi, Muhammad Irwan (Insan Cita Bongaya Research Journal, 2025)
This study aims to test and analyze the influence of premium income and underwriting results on the company's profit. The research was conducted on insurance companies listed on the Indonesia Stock Exchange which amounted to 15 companies with the number of documents in the form of financial statements observed for 3 years, so that the number of documents (observation data) was equal (15 x 3) = 45 financial statement documents. The data collection method uses documentation in the form of financial statements. Multiple linear regression data analysis techniques with SPSS application. The results of the study show that investment results have no effect on the company's profits. The results of underwriting have no effect on the company's profit. Keywords: Investment yield, underwriting yield, company profit